Changes of Red Blood Cell Surface Markers in a Blood Doping Model of Neocytolysis. (1st June 2009) - Chang, Chung-Che; Chen, Yayan; Modi, Kapil; Awar, Omar G.; Alfrey, Clarence P.; Rice, Lawrence
Abstract : Background: Neocytolysis, the selective hemolysis of young circulating red blood cells (RBCs), contributes to the physiologic control of red cell mass and to pathophysiologic phenomena such as anemia of renal disease, anemia after spaceflight, and blood doping by athletes. Progress in understanding the process is hampered by the lack of established markers to distinguish young from older RBC. Methods: Twelve potentially informative RBC surface markers were assayed by flow cytometry in normal blood samples, and 4 were preferentially expressed in young RBC. To create a model of neocytolysis, 3 normal volunteers had recombinant human erythropoietin (rhEpo) administered until mild erythrocytosis occurred, then were studied upon rhEpo withdrawal. Results: Neocytolysis ensued that most evident from a rapid rise in serum ferritin as the iron from young RBC was transferred back to stores. Five additional volunteers had surface markers monitored during and after rhEpo administration. Three subjects with marginal baseline iron stores had blunted response to rhEpo, no significant neocytolysis, and no change in RBC surface marker expression. Two subjects with adequate baseline iron stores developed erythrocytosis followed by neocytolysis. Decreased expression of CD44 (homing-associated cell adhesion molecule) and CD71 (transferrin receptor) seemed to correlate best with neocytolysis; CD35 (complement receptor) less so. Of note, further studies are needed to determine if these changes are causative of red cell destruction. Conclusion: This study begins to establish a human model of neocytolysis, to establish markers differentiating young and old RBC, and to establish a basis for better definition of the process. Although our study is preliminary, the results support the possibility that flow could be useful to detect blood doping because neocytolysis should predictably occur in athletes who surreptitiously blood dope.